Smart management system for monitoring and control of infant baby bed - Ali Sachit Kaittan; Siraj Manhal Hameed; Nisreen K. Ali; Mohammed Hasan Ali (Institute of Advanced Engineering and Science, 2020)
Step by step the innovation likewise becomes exceptionally quick and the human makes it. Thus, it is imperative to take care of the people to come, a unique consideration ought to be appeared to them particularly indulges. This paper manages plan and usage of intelligent child support framework which is extraordinary blessing to guardians in this century In this work a baby bed with intelligent system was be designed and implemented . many sensors where be used to monitor the baby behavior . the component of this project consist of a smart camera , moisture sensor , sensitive Dc Motor and WiFi system.